The reactions of KTM personnel towards the expected privatisation of KTM - Sahat, Azeni; Ahmad, Mohamad Azman; Elias, Siti Mona; Ahmad, Haslinawati; Reduan, Fatimah (1987)
This study was carried out to examine the reactions of Keretapi Tanah Melayu (KTM) personnel towards the expected privatisation of the organisation. The purpose of the research was to identify the level of awareness, understanding, and perception among employees regarding the government’s privatisation plan and its possible effects on their work environment. Data were collected through structured questionnaires and personal interviews with KTM staff from different departments at the headquarters in Kuala Lumpur. The findings show that most employees were aware of the upcoming privatisation, but many were unsure about its impact on their job security, benefits, and working conditions. Nevertheless, some respondents believed that privatisation could improve management efficiency and service quality. The study concludes that effective communication and employee participation are important to ensure a smooth and positive transition process for KTM.